Self-Assembly, Interfacial Nanostructure, and Supramolecular Chirality of the Langmuir-Blodgett Films of Some Schiff Base Derivatives without Alkyl Chain. (14th April 2013) - Jiao, Tifeng; Xing, Ruirui; Zhang, Qingrui; Lv, Yaopeng; Zhou, Jingxin; Gao, Faming
Abstract : A special naphthyl-containing Schiff base derivative, N ,  N ′ -bis(2-hydroxy-1-naphthylidene)-1, 2-phenylenediamine, was synthesized, and its coordination with various metal ions in situ at the air/water interface has been investigated. Although the ligand contains no alkyl chain, it can be spread on water surface. When metal ions existed in the subphase, an interfacial coordination between the ligand and different metal ions occurred in the spreading film, while different Nanostructures were fabricated in the monolayers. Interestingly to note that among various metal ions, only the in situ coordination-induced Cu(II)-complex film showed supramolecular chirality, although the multilayer films from the ligand or preformed complex are achiral. The chirality of the in situ Cu(II)-coordinated Langmuir film was developed due to the special distorted coordination reaction and the spatial limitation at the air/water interface. A possible organization mechanism at the air/water interface was suggested.